The East African Muslim welfare society (1945-1968): the case of Tanzania - Juma, Juma Khamis; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
This historical study focuses on identifying the East African Muslim Welfare Society since the time of the European colonial rule which started the beginning of the Christian domination in the region. The EAMWS was a multiracial Muslim organization in East African region. Muslims, regardless of their colour, tribes, sects and geographical differences, cooperated in primary things for the sake of their development. The society was established primarily for Muslim progress. The aim and objectives of EAMWS focused on preparing Muslims to survive in their environment and the hereafter. The study was conducted to find out the development of this Society since its formation in 1945 up to its abolishment in 1968. This research used various techniques to collect primary and secondary data. Interviews, participatory group discussion, field survey, observation check list and documentary review were used. The study has shown a number of Muslim social developments and their impact in Tanzania that were inculcated by this association since its establishment. During its time, the administration of the society contributed a lot to the economic and social development of the Muslims in the region. The finding shows a number of projects that were established in different areas for the sake of Muslim development which included primary and secondary school buildings, dispensaries, mosques, water reservoirs and wells. After its headquarters had transferred from Mombasa, Kenya to Dar es Salaam, Tanzania in 1961, the EAMWS started to face numerous challenges from the nationalist government led by Mwalimu Julius Kambarage Nyerere. Muslim political leaders as well as EAMWS leaders in Tanzania became enemies of Mwalimu Nyerere and his government because of their religion and the Muslim association. The Christians observed that, Islam developed through their organization that hindered their own development. They used political power so that they can stop the Muslims. Despite the efforts carried out by the Muslim society under the EAMWS leadership from 1961-1968, the association entered into a crisis that led to the abolishment by the Mwalimu Nyerere government and divided the Muslim communities in the region. Muslims lost political domination and remained second class citizens in their country despite having a larger population than Christians. They lost higher education opportunities and political posts. However, the time has come for Muslim societies to revive the Muslim association in the East African region.